Scanning Electron Microprobe Characterization of Air Filters from the Kavadarci Town and Tikveš Valley - Boev, Ivan; Šijakova-Ivanova, Tena; Mirakovski, Dejan (Geologica Macedonica, 2013)
The paper presents data from SEM characterization of Air Filters from Kavadarci town and Tikveš valey, Republic of Macedonia. Several filters from air pumps were submitted for characterization of particulate matter by Scanning Electron Microscopy (SEM) / Energy Dispersive Spectroscopy (EDS).The method of individual particle analysis provides important information about the composition and morphology of the particles, information that otherwise cannot be obtained by bulk analysis methods. The SEM–EDS technique is a valuable tool for the characterization of particles of less than 10 μm (PM10). Additionally, the identification of the morphology and chemical composition of these particles provides valuable information for the determination of their origin. EDS analyses revealed that the filters contained several aluminosilicate phases, including illite, plagioclase, quartz, and possibly amphibole/pyroxene and chlorite. Other phases observed were calcite, gypsum, iron oxides/hydroxides, chromites, silver minerals, and metallic phases. Minor nickel was found associated with metal oxides and stainless steel. No indicated of fibrous materials.